Modular Robot System for Maintenance Tasks in Large Scientific Facilities. (26th November 2013) - Pagala, Prithvi Sekhar; Baca, José; Ferre, Manuel; Aracil, Rafael
Large scientific facilities such as particle accelerators are scenarios that require continuous maintenance and specific type of interventions. The intervening personnel are sometimes required to work exposed to residual radiation. The inclusion of robotic systems into these environmental conditions are being encouraged to increase the availability of the facility and reduce personal radiation doses. However, this scenario presents challenging conditions for robotic systems in terms of structural, equipment and environmental conditions. This paper addresses the design of a modular robotic system as an alternative to conventional robots to overcome the challenges. This work also explores the various capabilities of the design along with its future possibilities. The SMART heterogeneous modular robot systems, prototype and simulation results are presented.